2012
DOI: 10.1016/j.amjsurg.2011.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Worsening severity of vitamin D deficiency is associated with increased length of stay, surgical intensive care unit cost, and mortality rate in surgical intensive care unit patients

Abstract: BACKGROUND Vitamin D deficiency is the most common nutritional deficiency in the United States. It is seldom measured or recognized, and rarely is treated, particularly in critically ill patients. The purpose of this study was to investigate the prevalence and impact of vitamin D deficiency in surgical intensive care unit patients. We hypothesized that severe vitamin D deficiency increases the length of stay, mortality rate, and cost in critically ill patients admitted to surgical intensive care units. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
136
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(153 citation statements)
references
References 32 publications
10
136
2
5
Order By: Relevance
“…This may result in even lower ''vitamin D levels'' as serum 25(OH)D is the accepted marker for vitamin D status. Several studies report low vitamin D levels to be a biomarker associated with sepsis severity, organ dysfunction and even mortality in critically ill patients (18)(19)(20)(21)(22)(23)(24).…”
Section: Vitamin D Deficiency In the Critically Illmentioning
confidence: 99%
“…This may result in even lower ''vitamin D levels'' as serum 25(OH)D is the accepted marker for vitamin D status. Several studies report low vitamin D levels to be a biomarker associated with sepsis severity, organ dysfunction and even mortality in critically ill patients (18)(19)(20)(21)(22)(23)(24).…”
Section: Vitamin D Deficiency In the Critically Illmentioning
confidence: 99%
“…As both are very prevalent in the general US population and even more pronounced in critically ill patients with TBI, in our opinion, atrisk patients should be routinely supplemented with vitamin D and omega3 fatty acids. In fact, vitamin D levels less than 17.8 ng/mL is shown to be associated with a 28% increased allcauses risk of premature death [6]. Equally important, omega3 fatty acid deficiency is associated with over 96,000 preventable deaths in the US annually according to a recent report from the CDC.…”
Section: Discussionmentioning
confidence: 97%
“…Vitamin D (classified as a vitamin) is actually a steroid hormone with pleiotrophic effects, which includes its action as immune modulator [6]. Of note, receptors for vitamin D are located on every cell and tissue of the human body including brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report that vitamin D deficiency in critically ill patients is associated with infection, the development of sepsis and acute respiratory distress syndrome (ARDS) and increased mortality rates (9,11,(14)(15)(16)(17)(18)(19)(20). Moromizato et al (21) found that serum vitamin D level below 16 ng mL -1 is associated with sepsis.…”
Section: Discussionmentioning
confidence: 99%